Dampak Kegiatan Penambangan Emas Terhadap Aspek Sosial Dan Aspek Ekonomi Masyarakat Di Desa Tanoyan Selatan Kecamatan Lolayan Kabupaten Bolaang Mongondow - Damolai, Hendrawan; Rengkung, Leonardus Ricky; Pakasi, Caroline Besty Diana (Sam Ratulangi University, 2024)
This research aims to determine the impact of gold mining activities on the social and economic aspects of the community in South Tanoyan Village. This research was conducted for 3 months starting from July to September 2023. The data used in this research is primary data. Primary data was obtained by direct interviews with sources. Sampling used the purposive sampling method. The criteria for the specified sample were the people of South Tanoyan Village who changed professions to become gold miners and carried out mining activities in the gold mining area, totaling 42 respondents. The research results show that gold mining activities have had a positive impact on the community's economy, as evidenced by increased income and ownership of adequate housing and transportation facilities. Gold mining activities also have a positive impact on increasing the workforce in South Tanoyan Village, where mining managed by the community requires quite a lot of workers to manage the mine. Apart from the positive impact of gold mining activities carried out by the community, it has a negative impact on the social community, this activity has a negative impact on agricultural land and the surrounding environment, the increase in illegal miners who carry out mining outside licensed areas and these activities result in accidents and fatalities, this occurs because of mining activities. Those managed by the community are still traditional.